MICE Tourism Development from a Local Economic Education Perspective - Junnurain Junnurain; Nining Yuniati (Civiliza Publishing, Indonesia., 2026)
With the development of the modern tourism industry, various forms of tourism have emerged that are not only oriented towards recreation but also towards business activities, one of which is MICE (Meetings, Incentives, Conferences, and Exhibitions) tourism. This study aims to identify the potential of Bima City for MICE tourism development, analyze the impact of MICE activities on local economic growth and improving community welfare, and identify internal and external factors that constitute the strengths, weaknesses, opportunities, and threats in the development of this sector. This study used a descriptive qualitative approach. The results indicate that the development of MICE (Meetings, Incentives, Conferences, and Exhibitions) tourism in Bima City has significant potential to become a strategic sector in driving local economic growth. Bima City already has several supporting factors, such as the availability of hotel facilities and meeting halls, regular seminars and cultural events, and support from the local government through the Bima City Tourism Office in developing the tourism sector. MICE activities have been proven to have significant economic impacts, both directly and indirectly, such as increased hotel occupancy rates, increased sales of MSME products, increased business opportunities, and increased economic turnover. This demonstrates that MICE tourism has a multiplier effect that can stimulate various local economic sectors.